Virtual education: Dental morphologies in a virtual teaching environment. Issue 10 (8th June 2020) - Liebermann, Anja; Erdelt, Kurt
Abstract: Objectives: Digital technology is already playing an increasingly important role in the education of students. The present investigation examined the acceptance of preclinical students for learning dental morphologies in virtual reality (VR). Methods: The creation of the VR dental teaching environment was divided into 3 sections: (a) generation of the digital data; (b) creation of the VR dental learning environment for tooth morphologies; and (c) evaluation by preclinical students through questionnaires combined with visual analogue scale and fixed‐answer options. Students of the Department of Prosthetic Dentistry of the University Hospital Munich were able to stay/interact in the VR dental learning environment for 10 minutes with VR headsets and hand controllers. The data were analyzed using the Kolmogorov−Smirnov test and exploratory data analysis using the median value and interquartile range. Results: Of the students, 34.9% stated that they understand dental morphologies much better, 57.1% better, and 7.9% equally well compared to using the traditional textbook. The students would be willing to spend about 500 euros privately for the VR equipment. The haptic and auditive teaching elements were evaluated more positively than the purely visual ones of the integrated information boards. Conclusions: Learning in the VR dental learning environment showed a high level of acceptance among all students and should be integrated as a fixed element in the dental curriculum. A further development for use independent of time and place is desirable.